Islandský rybolov jako národní zájem a jeho prosazování v zahraniční politice - Tůmová, Kateřina (Univerzita Karlova, Fakulta sociálních věd, 2016)
Presented thesis analyzes the Icelandic fisheries as a national interest and its role in foreign policy. Importance of fisheries confirms the fact that in the first half of the twentieth century marine products accounted for over 90% of Iceland's exports and the Icelandic economy was fully dependent on one sector. Gradual diversification of the economy in the seventies, however, caused a decline in exports of fish products to one-third of total exports. The thesis assumes that the Icelandic fisheries have a significant impact on foreign policy, even though its economic importance is declining. The research is carried out on three historical events, such as the cod wars in the fifties and the seventies, mackerel dispute in 2010 and the withdrawal of Iceland's application to the EU in 2015. It would be expected that due to the economic ties and Icelandic membership in international organizations (NATO, EFTA) the Icelandic government would primarily seek peaceful solutions in international conflicts. However, it could be observed in the Icelandic case that due to the pressure of the domestic politics the government does not respond as it would be expected. According to the neoclassical realism the thesis should verify a hypothesis that in a case of security threat, the Icelandic government will give. Diplomová práce analyzuje islandský rybolov jako národní zájem a jeho roli v zahraniční politice. Důležitost rybolovu potvrzuje fakt, že v první polovině dvacátého století tvořily mořské produkty přes 90 % islandského vývozu a islandská ekonomika byla plně závislá na jednom sektorovém odvětví. Postupná diverzifikace ekonomiky v sedmdesátých letech však způsobila pokles exportu rybích produktů až na jednu třetinu celkového vývozu. Práce předpokládá, že islandský rybolov má zásadní vliv na zahraniční politiku, i přestože jeho ekonomický význam klesá. Výzkum konkrétně probíhá na třech historických událostech, jakými jsou tresčí války z padesátých a sedmdesátých let, makrelová roztržka z roku 2010 a stažení islandské ...